(untitled) (Research Nepal Journal of Development Studies, 2019)
Infrastructures development is the backbone of a country’s economy. The developing countries like Nepal have to rely upon foreign assistance for the constructions of its mega projects, which need high investment cost, technology, and capable human resources. On this scenario, China government had assisted Nepal in building the eight lanes wide and ten kilometers long Koteswor to Kalanki section of the ring road. This paper describes how local road beneficiaries in Nepal perceive the construction work based on the Chinese model and their understanding on foreign aid development. The paper is based on a qualitative study with an interpretative case study design. The study has revealed that though the development aid policy of the developed nations is useful to maintain the cordial relations with the other developing nations, but at the same time, the people-centered development should not be undermined under this whole process. The explorations of this research are useful in framing appropriate plans and policies for the governments to orient the foreign aid development as per the needs of a larger section of people.